Effects of molecular weight on microfluidic separation - Kien, Dao Duy; Don, Nguyen Xuan (Vietnam Journal of Science and Technology, 2021)
the molecular weight effects the diffusion of molecules in the interface of laminar flow form in a microfluidic channel. Two mixtures of PS with anisole and PEG were used to evaluate the molecular weight effect on the microfluidic separation. Also, the separation of a low molecular weight substance of anisole from the mixture with a high molecular weight substance of PS is proved experimentally. However, the separation of PEG from the mixture with PS remained difficulty. More information about diffusion in microfluidic channel and can be applied to polymer science and separation fields.